Digitalisasi Wisata Desa: Pelatihan E-Ticket Untuk Kemudahan Kunjungan Di Desa Cisantana - Dian Ade Kurnia; Kaslani; Cep Lukman Rohmat (CV. Multi Kreasi Media, 2022)
Local tourism development is an important effort to support economic growth and sustainability at the village level. Cisantana Village, with its abundant natural and cultural riches, has great potential to develop the tourism sector. However, to achieve its potential, efficient and transparent management is needed. One of the proposed solutions is through the use of a tourist e-ticket application. This situation analysis will describe the location of partners, cases that have occurred, social and cultural aspects, special problems faced, service methods or approaches used, as well as the implications of the results of service to the community . Cisantana Village is located in a rural area that has extraordinary natural and cultural tourism potential. Tourists often come to this village to enjoy the natural beauty, interact with local residents, and experience the rich traditional culture. However, in recent years, increasing tourist interest has also led to complex management problems. Cases that have occurred are a surge in tourist visits that are not well organized, ticket sales that are difficult to monitor, and difficulties in understanding the magnitude of the impact of tourism on the community. As a result of this community service, we also held a successful marketing campaign to promote the use of e-ticketing to tourists. Through social media, village websites, and physical promotional materials, the benefits of e-ticketing are clearly communicated. Travelers are provided with information on how e-ticketing can save them time, avoid long queues, and provide a more comfortable visiting experience. The results of this community service are very satisfying, with a significant increase in tourist visits and positive feedback from users. The digitalization of village tourism through e-ticketing training has opened new doors to ease and comfort in enjoying the charm of Cisantana Village.